1992
DOI: 10.3109/00365519209090124
|View full text |Cite
|
Sign up to set email alerts
|

Levels of calprotectin (leukocyte L1 protein) during apheresis

Abstract: The plasma concentration of calprotectin was measured before, during and after apheresis in patients with Guillain-Barré Syndrome (GBS), Waldenstrøm's syndrome or hypercholesterolaemia and in healthy donors of platelets. Increased calprotectin levels were found after plasma exchange in the Waldenstrøm's syndrome patients, probably caused by release of the protein from activated leukocytes. The decreased calprotectin values observed in the other patients, may be due to plasma dilution. Unexpectedly, the GBS pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The 27E10 antigen is known to be upregulated by interferon-γ (Zwadlo et al, 1986), and interferon-γ-secreting inflammatory T cells may induce this phenotype in Guillain-Barré syndrome and CIDP nerves. It has also been shown that the soluble form of the 27E10 antigen is increased in the serum of Guillain-Barré syndrome patients prior to plasma exchange (Hetland et al, 1992). Changes in extracellular matrix composition may also account for phenotype differentiation (Mahnke et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The 27E10 antigen is known to be upregulated by interferon-γ (Zwadlo et al, 1986), and interferon-γ-secreting inflammatory T cells may induce this phenotype in Guillain-Barré syndrome and CIDP nerves. It has also been shown that the soluble form of the 27E10 antigen is increased in the serum of Guillain-Barré syndrome patients prior to plasma exchange (Hetland et al, 1992). Changes in extracellular matrix composition may also account for phenotype differentiation (Mahnke et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…15 Stimulation of PMN with these ligands triggers a range of biological activities including chemotaxis, superoxide formation, enzyme release, and aggregation. [16][17][18][19] Previously, we found that the plasma concentration of calprotectin increased after plasma apheresis in patients with Waldenström's syndrome, 20 and suspected that this was related to the increase in complement activation products seen in one of these patients. 21 Recently, Garred et al showed that the release of calprotectin coincided with activation of complement during major surgery.…”
mentioning
confidence: 99%